LANDSCAPE MANAGEMENT IN THE ISLAMIC CENTER AREA, BEKASI - Fadhilah Cahya Rahmani; Qurrotu ‘Aini Besila; Fauzi, Reza (Universitas Trisakti, 2024)
Islamic Center is generally a place of guidance and worship for Muslims who have supporting facilities for worship activities carried out in the Islamic Center area. For a public facility Islamic Center should have areas that are comfortable to use by users both indoors and outdoors. In order to create a good outdoor space functionally and aesthetically, good landscape management is needed, starting from the assignment system to the maintenance implementation system. The problem that occurs at the Bekasi Islamic Center is the ineffectiveness of the workforce assignment in the management and physical maintenance of the outdoor space area, the purpose of this study is to produce recommendations for work effectiveness for the physical maintenance unit at the Bekasi Islamic Center. The method used is a qualitative method by analyzing data through interviews, observation and data collection. The expected results can provide recommendations related to physical maintenance activities at the Bekasi Islamic Center so that they can be in accordance with applicable standards and can affect the effectiveness of the work performed.